Методика расчета размеров кластера - Дулгиер, А. С.; Тур, Б. С.; Черкас, Ю. В. (ХНУРЭ, 2009)
The given work is devoted to analyses methods of clusters size determination. Shows qualities and imperfections of this techniques. Describes in which situation it is better to use one method and in which another.